Resveratrol improves salivary dysfunction in a non-obese diabetic (NOD) mouse model of Sjögren’s syndrome - Inoue, Hiroko (J Clin Biochem Nutr, 2016)
Resveratrol is a natural polyphenol produced by plants in response to environmental stress. This compound has been shown to have pharmacological effects against a wide range of diseases including neurological, hepatic, cardiovascular and autoimmune conditions. The non-obese diabetic (NOD) mouse, in which loss of lacrimal and salivary gland function occurs, has been studied as an animal model for Sjögren’s syndrome. In this study, we confirmed that administration of resveratrol results in increased secretion of saliva in NOD mice. Although resveratrol enhanced Sirt1 activity, inflammatory cell infiltration was not affected. Moreover, expression of the anti-inflammatory cytokine IL-10 in salivary glands was enhanced in the resveratrol-administered group. Thus, we confirmed a novel therapeutic effect for resveratrol on salivary dysfunction in Sjögren’s syndrome.